Understanding psychology - Feldman, Robert S. (Robert Stephen), 1947- (New York, NY : McGraw-Hill Education, 2021)
"14th edition of Understanding Psychology has relied heavily and benefited substantially from the advice of instructors and students from a wide range of backgrounds. Effective introduction to a discipline must be oriented to students informing them, engaging them, and exciting them about the field and helping them connect it to their worlds. All these goals are achieved in Understanding Psychology, 14/e"--
Revised edition of the author's Understanding psychology, c2018.
Includes bibliographical references and index.
ESS
Trim Education
Keywords: Psychology